Integrating usability in automotive navigation user interface design via Kansei Engineering - Syed Mohamed, Muhammad Syafiq; Mohd Tamrin, Shamsul Bahri; Abdul Rahman, Ahmad Rizal; Mat Said, Aini; Abdul Jalil, Nawal Aswan (Canadian Center of Science and Education, 2016)
Balancing user requirements as well as usability requirements can be an exacting task for designers. Automotive navigation user interfaces are of no exception. The aim of this study was to integrate the concept of usability in the design process for automotive navigation user interfaces. A modified Kansei Engineering approach was used in order to define the concept of usability for automotive navigation user interface. Both regular and professional Malaysian drivers participated in the Kansei evaluation experiment (n=118). Results were analyzed with Principal Components Analysis (PCA) as well as Partial Least Squares (PLS) method. A finalized list of design specifications was developed and the design specifications were then used to develop a new automotive navigation interface design.